The Correlation of The Age and Length of Stay with The Compliance of Beef Cattle Farmers Norms: Case Study in Final Waste Disposal of Jatibarang, Semarang City - Muatip, Krismiwati; Purwaningsih, Hermin; Priyono, Agus; Nuskhi, Muhammad; Setiana, Lucie; Putra, Aditya Permana (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
The study was conducted in the final waste disposal (TPA) Jatibarang, Kedungpane, Mijen, Semarang. A survey was conducted, targeting the beef cattle farmers who pastured their cattle in the TPA Jatibarang, Semarang. The observed variables were age (X1), education background (X2), length of stay (X3), total cattle owned (X4), and the farmer’s norm compliance (Y1). Purposive sampling was used to determine the sample of regions. Total respondents were determined by simple random sampling, selecting 70 out of 350 farmers (20%). The result of the analysis showed that 78.57% farmers were at their productive age (20-55 years old), 64.30% had elementary education background, 74.29% had been farming for over 14 years, and 62.86% had fewer than seven cattle. The farmers also showed a sound moral compliance. The result of spearman rank showed a non-significant correlation between age and length of farming experience with norm compliance. Age was negatively correlated with norm compliance, but education background and total cattle owned were significantly correlated with norm compliance, showing a correlation value of 0,248* and 0,610*, respectively.